If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9x + 13y + -3y + 5x = 0 Reorder the terms: -9x + 5x + 13y + -3y = 0 Combine like terms: -9x + 5x = -4x -4x + 13y + -3y = 0 Combine like terms: 13y + -3y = 10y -4x + 10y = 0 Solving -4x + 10y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10y' to each side of the equation. -4x + 10y + -10y = 0 + -10y Combine like terms: 10y + -10y = 0 -4x + 0 = 0 + -10y -4x = 0 + -10y Remove the zero: -4x = -10y Divide each side by '-4'. x = 2.5y Simplifying x = 2.5y
| 5-(3b-5)=-17 | | (X*4)+(y*2)=360 | | 9=r+7 | | 8x-4y=-1 | | 6x+4x-45=60-5x | | 51-5x=19+11x | | 5r+11-2r-1= | | -23=-6p-7p | | 3z+4=4 | | 0=4.9t^2-11t-92 | | 23x+4(x+1)=27(x+1)-23 | | 4x+3(4x+7)=133 | | 6(9+x)=7x-4 | | 0=-4.9t^2+11t-92 | | 9(10x-1)+1=20 | | -5-7(1+8x)=268 | | 15m-2+4m-17= | | 18v=954 | | 5n=7+3x | | 3x+2(3-x)=9 | | (-6)(-2)(8r)= | | (fg)(x)=(x-8)(4x^2) | | 0=-x^2+100x-2400 | | 2x-1=-x+15 | | 7x-y+18y-4x-15y= | | (2g+7)=(3g-5g+2) | | .5x-24=3x-46 | | -8(x+4)=7(2x+8) | | 68x-60=80 | | 2(5n-3)-n-2= | | 68x-60= | | 8x-13y+5y+x= |